(untitled) - Eugene F. Brigham; Eugene F. Brigham; Joel F. Houston; Dana Aberwald Clark (Mason, Ohio, 2004)
Prepared by Eugene F. Brigham and Joel F. Houston The Study Guide lists the key learning objectives for each chapter, outlines the key sections, provides self-test questions, and provides a set of problems similar to those in the text and the Test Bank, but with fully worked-out solutions
Keywords: Corporations; Corporations